Penerapan Metode Analytical Hierarchy Process Dalam Menentukan Teknisi Terbaik Pada PT. Sejahtera Buana Trada - Nur Fahmi Azis; Hendri Irawan (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2022)
PT Sejahtera Buana Strada is the main Suzuki car dealer in Indonesia, which operates directly under the auspices of PT Suzuki Indomobil Sales as the ATPM (Single Agent for Brand Holders). Once in six months, the selection process for the best technicians is carried out. This mechanism aims to provide rewards and increase the motivation for the technicians' performance. However, the current approach is not optimal and has several obstacles. The problem faced is that the head of the workshop still takes a long time to determine the best technician. It is because the head of the workshop must analyze each technician's assessment form, which causes delays in submitting the best technician's report to the leader. In addition to other problems, the leadership is difficult to find out the history of the best technicians because the archives of the best technicians have not been stored properly. The decision support system was built to make it easier for the head of the workshop to make a decision. The system can decide by considering the criteria that the head of the workshop has determined. Therefore, a decision support system web-based application on PHP and MySQL as the database to solve this problem. This application uses the Analytical Hierarchy Process (AHP) method. The reason for using this method is because there is an eigenvector concept to carry out the priority ranking process for each criterion based on a pairwise comparison matrix. As a result, the process of assessing the best technicians can be carried out quickly, and leaders can review the history of the best technicians.